Analisis Line Balancing untuk Mencapai Efisiensi Kerja dengan Pendekatan Heuristic (Study Kasus: CV. XYZ) - Amanah Isnaini; Herlina Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. XYZ is a promotional media manufacturing company facing workload imbalance in its neon box production process, particularly at the assembly work center. This study aims to analyze production line balancing using the Ranked Positional Weight (RPW), Kilbridge-Wester Heuristic, and Largest Candidate Rule (LCR) methods. The research data consist of 30 work elements with a total standard time of 3.143.527 seconds. The results show that the RPW method obtained a line efficiency of 80.15%, balance delay of 19.85%, and smoothing index of 356.712 seconds. The Kilbridge-Wester method resulted in a line efficiency of 72.14%, balance delay of 27.86%, and smoothing index of 481.83 seconds. The LCR method provided the best performance, with a line efficiency of 90.17%, balance delay of 9.83%, and smoothing index of 176.77 seconds. Therefore, LCR is recommended as the proposed line balancing improvement, supported by adding two workers to the assembly station to reduce bottlenecks.